A fiduciary marker-based framework to assess heterogeneity and anisotropy of right ventricular epicardial strains in the beating ovine heart. (26th October 2018) - Meador, William D.; Malinowski, Marcin; Jazwiec, Tomasz; Goehler, Matthew; Quay, Nathan; Timek, Tomasz A.; Rausch, Manuel K.
Abstract: Quantifying ventricular deformation in health and disease is critical to our understanding of normal heart function, heart disease mechanisms, and the effect of medical treatments. Imaging modalities have been developed that can measure ventricular deformation non-invasively. However, because of the small thickness, complex shape, and anatomic position of the right ventricle, using these technologies to determine its deformation remains challenging. Here we develop a first fiduciary marker-based method to assess heterogeneity and anisotropy of right ventricular epicardial strain across the entire free wall. To this end, we combine a high-density array of sonomicrometry crystals implanted across the entire right ventricular epicardial surface with a subdivision surface algorithm and a large deformation kinematics framework. We demonstrate our approach on four beating ovine hearts and present a preliminary regional analysis of circumferential, longitudinal, and areal strain. Moreover, we illustrate maps of the same strains across the entire right ventricular epicardial surface to highlight their spatial heterogeneity and anisotropy. We observe in these animals that RV epicardial strains vary throughout the cardiac cycle, are heterogeneous across the RV free wall, and are anisotropic with larger compressive strains, i.e., contraction, in the longitudinal direction than in the circumferential direction. Average peak compressive strains vary by region between −3.34% and −8.29% in circumferential direction, and −4.02% and −10.57% in longitudinal direction. In summary, we introduce an experimental framework that will allow us to study disease- and device-induced deformations, and long-term consequences of these deformations, including heterogeneous and anisotropic effects.